PENGARUH KUALITAS PELAYANAN, HARGA, DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN (Survei pada Konsumen The Hidden Place By Jox’s Surakarta) - Anugrah Nadia Sukma; Sumaryanto Sumaryanto; Retno Susanti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the importance of the influence of service quality, price, and store atmosphere on consumer satisfaction at The Hidden Place by Jox's Surakarta. This type of research is a consumer survey, the type of data used is qualitative data and quantitative data. Data sources used are primary data and secondary data. The population in this study are all consumers at The Hidden Place by Jox's Surakarta whose numbers are not known with certainty. Samples amounted to 100 respondents with accidental sampling technique. Data collection techniques using observation, questionnaires, and literature studies. The instrument test uses a validity test and a reliability test. The classic assumption test uses tests: Multicollinearity, Autocorrelation, Heteroscedasticity, and Normality. Data analysis techniques: multiple linear regression analysis, t test, F test, and the coefficient of determination (R2 ). The result of this study indicate that the service quality significantly influence consumer satisfaction in The Hidden Place By Jox’s Surakarta, price significantly influence consumer satisfaction in The Hidden Place By Jox’s Surakarta, and store atmosphere significantly influence consumer satisfaction in The Hidden Place By Jox’s Surakarta. Three variables contributed 31 percent.